Pengaruh Motivasi terhadap Kinerja Guru di SDN 091561 Afd.A Pagar Jawa - Kartini Kartini; Anggiat Sinurat; Ulung Napitu (Journal on Education, 2023)
This study was to determine the effect of motivation on teacher performance at SDN 091561 Afd.A Pagar Jawa. motivation is an action taken to encourage one's morale with the aim of increasing performance in achieving a goal. By increasing the performance of teachers in carrying out their duties as teachers, mentors and educators, they can improve the quality of graduates in accordance with the educational goals of educating the nation's children. This study uses a qualitative approach by describing and explaining motivation in improving teacher performance. To describe and describe the data by reviewing some of the expert opinions that have been described. So by using a qualitative approach this research is expected to obtain comprehensive facts about the effect of motivation on teacher performance at SDN 091561 Afd. A Java Fence. Performance is the result achieved from an action taken by a person both individually and in groups, which can be in the form of achievement or failure in achieving the set goals. Teachers are Educators who have the task of educating, teaching and guiding students both formal and non-formal education with the aim of increasing the intelligence of students. Meanwhile, according to Sugiyono (2019: 69) the independent variable (independent variable) is a variable that influences or is the cause of the change or the emergence of the dependent (bound) variable. The independent variables (X) in this study are: Motivation. The dependent variable (tied) is the variable that is affected or becomes the result, because of the Free Variables. As for the Dependent Variable in (Y) in this study is Teacher Performance. The data collection technique used in this study is library research (Library Research) where library research is the activity of collecting research-related materials from scientific journals, literature, and authors.